P63 Accuracy (Validation) of Central Blood Pressure Measurement Using the Sphygmocor Xcel-cuff Device - Martin Schultz; Dean Picone; Matthew Armstrong; Andrew Black; Nathan Dwyer; Philip Roberts-Thomson; James Sharman (Artery Research, 2020)
Background: Numerous devices purport to measure central aortic BP as distinct from conventional brachial BP. This study aimed to determine the accuracy (validation) of the Sphygmocor Xcel-cuff device (AtCor Medical, Sydney, Australia) for measuring central BP. Methods: 330 patients (mean age 61.3 ± 10.6 years) undergoing coronary angiography had simultaneous measurement of invasive aortic BP and non-invasive cuff-derived central BP using the Xcel device (total n = 552 individual comparisons). Methods were undertaken according to Artery Society guidelines and several calibration techniques to derive central SBP were examined. Results: Central SBP was significantly underestimated, and with wide variability, when using the default calibration of brachial cuff SBP/DBP (−7.7 ± 11.0 mmHg). Similar wide variability was observed using other calibration methods (cuff 33% form-factor MAP/DBP, −4.4 ± 11.5 mmHg; cuff 40% form-factor MAP/DBP, 4.7 ± 11.9 mmHg; cuff oscillometric MAP/DBP, −18.2 ± 12.1 mmHg). Only calibration with invasive aortic integrated MAP/DBP resulted in a mean difference ± SD (3.3 ± 7.5 mmHg) within the minimum tolerable error of ≤5 ± ≤8 mmHg. The difference between brachial cuff SBP and invasive aortic SBP was 3.3 ± 10.7 mmHg. A subsample (n = 151) analysis to determine the accuracy of central-to-brachial SBP amplification, showed this to be over-estimated by the Xcel device (4.3 ± 9.1 mmHg, p = 0.02). Conclusion: Irrespective of calibration technique, the Sphygmocor Xcel-cuff device does not pass the Artery Society accuracy (validation) criteria for non-invasive measurement of central BP. Further accuracy refinements of this device are required.